Resting immuno-hematological profiles associated with regular futsal training in adolescent futsal players: an exploratory ABO-stratified cross-sectional study - Danil Dychko; Elena Dychko; Vladislav Dychko; Iryna Kushakova; Yulia Klimenko (Academic Journal of Health Sciences, 2026)
Objectives: This exploratory cross-sectional study assessed resting immuno-hematological profiles in 13–14-year-old boys engaged in regular futsal training and compared these profiles across ABO blood groups. Methods: The sample included 96 clinically healthy boys: 48 futsal players and 48 age- and ABO-frequency-matched controls without systematic sports training. The ABO distribution was identical in the futsal and control groups. Morning fasting capillary blood samples were collected during the intertraining period. Four-week training exposure was characterized using attendance logs, session-RPE records, and match documentation. Biological maturation was assessed using physician-rated Tanner staging and examined in sensitivity models. Holm correction was applied separately to leukocyte comparisons and primary and secondary interaction test families. Results: Leukocyte parameters and integral immuno-hematological indices were analyzed. The primary outcomes were the cellular reactivity index, leukocyte intoxication index, and neutrophil-to-lymphocyte ratio. Secondary outcomes included the nonspecific reactivity index and immunological reactivity index. After Holm correction, futsal players differed from controls in neutrophil, lymphocyte, eosinophil, and basophil proportions. ABO-stratified analysis showed group-specific patterns. O(I) and A(II) futsal players had higher cellular reactivity than controls. B(III) futsal players had lower cellular reactivity and a higher leukocyte intoxication index. NLR values were descriptively higher among futsal players across all ABO groups. AB(IV) futsal players showed an intermediate mixed profile. Training-by-ABO interactions remained significant for the cellular and leukocyte intoxication indices, but not for the NLR. Adjustment for Tanner stage did not materially alter the primary training status × ABO interactions. Conclusions: The results suggest ABO-related variability in resting immuno-hematological profiles among adolescent futsal players. These cross-sectional findings do not establish causal effects of futsal training. Longitudinal studies are needed to determine whether these profiles are associated with recovery, illness risk, performance, or training-load tolerance.